The Markan Narrative's Use of the Old Greek Text of Jeremiah to Explain Israel's Obduracy - Larry Perkins (Tyndale Bulletin, 2009)
A close reading of the Septuagint (LXX) translation of Jeremiah in conjunction with a careful examination of Markan contexts where Jeremiah materials occur reveals that Jeremiah’s prophetic message influences the Markan portrayal of Jesus’ words and deeds, especially to explain Israel’s obduracy. By examining specific contexts in Mark’s narrative (chs. 8, 11, 13, 14) where potential intertextual linkages with the Greek version of Jeremiah’s prophecy occur I demonstrate the potential contribution of the Greek version of Jeremiah’s material to our understanding of Mark’s purpose. His use of Jeremiah material seems to focus almost exclusively on aspects of opposition that Jesus experienced. The general theme of Israel’s obduracy, illustrated by the temple cleansing incident, the parable of the tenant farmers, and the prophecy about the destruction of Jerusalem and the temple seems to provide the thread that the Markan author finds useful to link with Jeremiah’s message.